Analysis of the problems of managing business processes of engineering companies in the implementation of investment projects - Gurenko, Anna; Gurenko, Sergey (Technology audit and production reserves, 2020)
The object of research is a business process management system of engineering companies. The paper considers the existing system of interaction between design institutes, engineering companies and manufacturing enterprises implementing investment projects. In particular, the differences in the construction of business processes in previously existing design institutions and modern engineering companies are identified. The research methodology is based on theoretical and methodological analysis of scientific literature, statistical methods, as well as observation, comparative method, description, measurement. The use of scientific research methods has revealed weaknesses and contradictions in the business process management system. The results of this research indicate that the development, verification and approval of design and estimate specifications are the main business process of engineering companies. It is proved that these business processes are an integral part of the investment project. Therefore, for the successful implementation of company projects, customers attract a large number of external contracting organizations – design, engineering, construction companies. The increase in the number of participants in the investment process significantly complicates the construction of business processes, which leads to an increase in the timing of development, verification and approval of design and estimate specifications. The analysis allows to identify the causes of inconsistencies when working with specification. The main reasons for increasing the verification time are systemic problems in organizing the interaction of project participants. It is determined that the pre-existing holders of archival design specification that provided comprehensive turnkey services have practically disappeared from the market. Contracting organizations appeared in their place, separated from large specialized design organizations. The created contracting organizations work in different versions of the software, therefore they created sets of documents of varying degrees of detail of design decisions. In general, it is recommended to optimize the docking of documents between participants in investment projects. The implementation of the proposed measures becomes possible in the context of the introduction of information technology based on joint teamwork to create an electronic model.